Risk factors associated with recurrence in patients undergoing orthognathic surgery: a scoping review - Garcia Fuster, Consuelo (2026)
Objectives: Recurrence is one of the main complications associated with orthognathic surgery. For this reason, the aim of this study is to identify risk factors for recurrence in patients who have undergone orthognathic surgery. Materials and Methods: A literature review was conducted in PubMed, Web of Science, and Scopus during May 2025. Articles from the last 5 years were selected, excluding narrative reviews, systematic reviews, meta-analyses, letters, opinion pieces, animal studies, or experimental models. Results: Out of 56 articles, 21 were removed due to duplication and 16 for not meeting eligibility criteria, resulting in 19 articles for final analysis. Among the risk factors mentioned in the literature, prominent contributors include positional changes at the temporomandibular joint, temporomandibular disorders associated with condylar morphological changes, tension and volumetric alterations of associated muscles, changes in occlusal plane inclination, and the magnitude of surgical movement. Conclusions: Risk factors exert different influences depending on the type of malocclusion, the combination of surgical techniques, and the approach employed. To establish causality, further clinical studies isolating variables and enabling long-term follow-up are necessary. These findings will provide scientific support for implementing necessary measures and selecting the optimal treatment to reduce recurrence risk, along with its associated economic, physical, and psychological costs.